Pengembangan Perangkat Pembelajaran Berbasis Budaya Bugis-Makassar Di SD Kota Makassar - Latri Aras; Ramlan Mahmud; Yusnadi Yusnadi; Bahar Bahar (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aimed at producing Buginese–Makassarese culture-based-mathematics instructional packages of Grade X students of SMA which were valid, effective, and practical. The packages were Lesson Plan, Student Book, and Student Worksheet. This study was research and development. The utilized developmental model within this study was modification and adaptation of 4-D model (Thiagarajan, 1974), which consisted of four stages, namely: (1) define; (2) design; (3) develop; and (4) disseminate. In collecting data, it was used: (1) a validation sheet of instructional package, (2) an observation sheet, (3) students’ responses, and (4) learning achievement test. The data was then analyzed utilizing the descriptive analysis.The research results indicate that the average scores of student book and student worksheet validities are in very valid category. Lesson plan is in valid category. Analysis of the effectivity of instructional package shows that the average of overall student activities is in the tolerance interval of an ideal time percentage, and most activities used in learning are to bend on group presentation, to ask a question, or to provide an assistance. In addition, students responded positively to the implementation of the instructional package and the practice of Buginese–Makassarese culture-based-mathematics instructional model as 95.74%. Further, students are in high category, although on the observation process to the development of cultural values of Buginese–Makassarese, particularly siri’ and pacce/pesse values, some of them are still in the category of starting to appear, but this criteria must not be satisfied. The analysis of the practicality of the instructional package is in good category.